2018
DOI: 10.1002/cbin.10997
|View full text |Cite
|
Sign up to set email alerts
|

The suppressive effect of soluble Klotho on fibroblastic growth factor 23 synthesis in UMR‐106 osteoblast‐like cells

Abstract: Fibroblastic growth factor 23 (FGF23) is a hormone secreted primarily by bone. FGF23 is elevated in the serum of chronic kidney disease (CKD) patients, but the exact mechanism is not well known. Klotho is identified as an aging suppressor, which is mainly expressed in the kidney, and the level of soluble Klotho is negatively associated with FGF23 in CKD. The aim of this study was to investigate the effect and possible mechanism of Klotho on FGF23 synthesis in osteoblast-like UMR-106 cells. UMR-106 cells were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…This hypothesis is supported by previous observations showing that Wnt activity is increased in Klotho knockout mice [89]. Ma et al observed that in UMR-106, a bone cell line, the addition of β-glycerophosphate increased the expression of Wnt target genes; the co-administration of β-glycerophosphate and sKlotho led to a decrease in FGF23 levels and a reduction in Wnt activation, suggesting that sKlotho could modulate osteogenesis and FGF23 production [90]. In this line, other authors have observed that secreted Klotho, through the inhibition of FGFR1 and ERK phosphorylation, can delay human mesenchymal stem cell differentiation into osteoblasts [91,92] (Figure 2).…”
Section: Fgf23-klotho and Wnt In Bonesupporting
confidence: 76%
“…This hypothesis is supported by previous observations showing that Wnt activity is increased in Klotho knockout mice [89]. Ma et al observed that in UMR-106, a bone cell line, the addition of β-glycerophosphate increased the expression of Wnt target genes; the co-administration of β-glycerophosphate and sKlotho led to a decrease in FGF23 levels and a reduction in Wnt activation, suggesting that sKlotho could modulate osteogenesis and FGF23 production [90]. In this line, other authors have observed that secreted Klotho, through the inhibition of FGFR1 and ERK phosphorylation, can delay human mesenchymal stem cell differentiation into osteoblasts [91,92] (Figure 2).…”
Section: Fgf23-klotho and Wnt In Bonesupporting
confidence: 76%
“…UMR106 osteoblast-like cells were chosen for our study because under physiological conditions, bone is the major site of FGF23 production [ 45 ] and these cells are a versatile tool employed in many studies to unravel the regulation of FGF23 [ 25 , 46 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to our study, two cytotoxic drugs with different cellular targets used in the treatment of several malignancies as well as apoptosis inducers PAC-1 and serum depletion stimulated Fgf23 gene expression in UMR106 osteoblast-like cells within 24 h. The effect was paralleled by a reduction in cell viability and proliferation as deduced from cell number. UMR106 osteoblast-like cells were chosen for our study because under physiological conditions, bone is the major site of FGF23 production [45] and these cells are a versatile tool employed in many studies to unravel the regulation of FGF23 [25,[46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%